The State of the Art on the use of mobile technologies in Basic Education: mapping of works written from 2016 to 2018 (Research, Society and Development, 2020)
This work addresses the use of mobile technologies in Basic Education. They are increasingly present in children, teenagers and young people's daily lives. The objective is to map some academic works related to this topic. Therefore, State of the Art research was used as methodology; and the data was constituted from research and information taken from the Catálogo de Teses e Dissertações da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), from the Revista Novas Tecnologias na Educação (RENOTE), and from the Annals of the 1st, 2nd and 3rd Simpósio Nacional de Tecnologias Digitais na Educação (SNTDE). On databases, these following descriptors were used: “mobile technologies”, “mobile technology”, “mobile devices”, “mobile device”, “mobile learning” and “mobile education”. Taking into account that mobile technologies include several types of devices, among them, cell phones, tablets and notebooks, some works were identified that deal with this term comprehensively, not only one of the particular devices. After applying a delimited selection in each one database, 19 works were found: 5 dissertations and 14 scientific articles. Some categories were identified in these works, such as: research objectives, methodological approach and pedagogical practices. The researched works used a qualitative methodological approach. Most of the pedagogical practices were focused on Elementary Education.